A new synthesis of amino substituted azolo[1,3,5]triazines via reaction of N1,N1-dimethyl-N2-azolylformamidines with cyanamide - Kalinin, D.; Kalinina, S.; Dolzhenko, Anton (The Japan Institute of Heterocyclic Chemistry, 2013)
The amino substituted triazine ring was annelated to aminoazoles using a new effective synthetic procedure. The method of preparation involved initial formation of azolylformamidines in the reaction of aminoazoles with N,N-dimethylformamide dimethyl acetal followed by the triazine ring closure with cyanamide affording therefore fused aminotriazines.